Incidental Finding of Urinary Bladder Retention on the 99mTc-Labeled Red Blood Cells Subcutaneous Radionuclide Venography. (August 2015) - Chang, Yi-Ling; Liu, Chih-Ting; Chu, Hsiu-Lan; Chen, Yu-Wen; Lin, Chia-Yang
Abstract : Abstract: We present a case with swelling of the lower extremities, shortness of breath, and hyponatremia. 99m Tc-labeled red blood cells subcutaneous radionuclide venography was performed to rule out deep vein thrombosis. Disturbed iliac venous flow and a photopenic lesion were noted in the lower abdomen on the planar imaging. SPECT/CT imaging revealed a hypodense lesion in the lower abdomen. Distended urinary bladder and retention were impressed. After approximately 4000 mL of urine was drained, symptoms were dramatically relieved, and improvement of hyponatremia was also observed.